Creating a foundation for the visualization of intracranial cerebrospinal fluid using photon-counting technology in spectral imaging for cranial CT - Klempka, Anna; Neumayer, Philipp; Schröder, Alexander; Ackermann, Eduardo; Hetjens, Svetlana; Clausen, Sven; Groden, Christoph (Diagnostics, 2024)
Background: Recent advancements in computed tomography (CT), notably in photon-counting CT (PCCT), are revolutionizing the medical imaging field. PCCT’s spectral imaging can better visualize tissues based on their material properties. This research aims to establish a fundamental approach for the in vivo visualization of intracranial cerebrospinal fluid (CSF) using PCCT. Methods: PCCT was integrated to distinguish the CSF within the intracranial space with spectral imaging. In this study, we analyzed monoenergetic +67 keV reconstructions alongside virtual non-contrast and iodine phase images. This approach facilitated the assessment of the spectral characteristics of CSF in patients who did not present with intra-axial pathology or inflamation. Results: Our findings illustrate PCCT’s effectiveness in providing distinct and clear visualizations of intracranial CSF structures, building a foundation. The signal-to-noise ratio was quantified across all measurements, to check in image quality. Conclusions: PCCT serves as a robust, non-invasive platform for the detailed visualization of intracranial CSF. This technology is promising in enhancing diagnostic accuracy through different conditions.
Gesehen am 24.04.2025